Analisis Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - sukarno, agus (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance effect of product quality and service quality on customer satisfaction, analyze the significance effect of product quality, service quality and customer satisfaction on customer loyalty and analyze the significance effect of product quality and service quality on customer loyalty with customer satisfaction as an intervening variable. This type of research is survey research. The population of this research is kindergarten as customers of Ceria Ramadhan at PT. Antero Mandiri Sentosa in Jombang Regency. A sample of 90 customers with a purposive sampling technique. Data sources use primary data and secondary data. Data collection methods used questionnaires and literature study. Data analysis techniques used path analysis. The results showed that product quality and service quality has a significant effect on customer satisfaction.. Product quality, servicee quality and customer satisfaction has a significant effect on customer loyalty. Product quality and service quality has a significant effect on customer loyalty with customer satisfaction as an intervening variable. Keywords: product quality, service quality, satisfaction, loyalty